Aromatic polyoxadiazole film and its preparation method and application

By optimizing the preparation process of POD film, the molecular weight and cyclization rate are improved, and a single-stage solidification bath with high concentration and low temperature and bidirectional stretching treatment are adopted, the "powder loss" problem of POD films in the process of carbonization and graphitization is solved, achieving high thermal conductivity and broader application prospects.

CN119285937BActive Publication Date: 2025-03-18HUNAN HAOBORUI NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411823967.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

Aromatic polyoxadiazole (POD) films are prone to "powder loss" during carbonization and graphitization, which affects the performance and application of materials.

Method used

By optimizing the preparation process of POD films, including controlling the reaction temperature, time and feeding method, improving the molecular weight and cyclization rate, using a single-stage solidification bath with high concentration and low temperature and bidirectional stretching treatment, POD films with high molecular weight, high cyclization rate, high orientation and high density are prepared.

Benefits of technology

It effectively solves the problem of "powder loss", improves the thermal conductivity and overall performance of the film, ensures the flatness and integrity of the supercrystalline graphite film, and enhances its application prospects in the consumer electronics field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285937B_ABST
    Figure CN119285937B_ABST
Patent Text Reader

Abstract

The present invention provides an aromatic polyoxadiazole film and a preparation method and application thereof, wherein the preparation method of the aromatic polyoxadiazole film comprises the following steps: using fuming sulfuric acid as a solvent and a dehydrating agent, terephthalic acid and hydrazine sulfate as monomers, and benzoic acid as a chain end-capping agent, adopting step-by-step feeding, carrying out a three-stage polycondensation reaction, and obtaining an aromatic polyoxadiazole resin solution; conveying it to a forming die head under pressure orientation, extruding it, obtaining an acid-containing primary cast film, and then solidifying and forming it in a single-stage coagulation bath to obtain a polyoxadiazole wet film; washing it, obtaining an acid-free polyoxadiazole wet film; and then biaxially stretching, and then performing a heat setting treatment to obtain the aromatic polyoxadiazole film. The aromatic polyoxadiazole film prepared by the present invention does not produce a "powder falling" problem after carbonization and graphitization, and the obtained supercrystalline graphite film has a smooth and uniform appearance, a more complete crystal structure, higher thermal conductivity, no pollution to electronic components, and good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an aromatic polyoxadiazole film for preparing non-powdering supercrystalline graphite, and a preparation method and application thereof. Background Art

[0002] With the advent of the 5G era, information technology, artificial intelligence, the Internet of Things and other fields have developed rapidly, and the functions of electronic products have gradually become integrated, complex, and miniaturized, which has led to the continuous increase in the power and integration of electronic products and the increasing power density. As a result, high heat generation and difficulty in timely discharge occur during their use. The long-term high-temperature operation of core components has seriously affected the stability, reliability and service life of electronic products. It is particularly important to solve the heat dissipation problem.

[0003] Traditional metal thermal conductive materials, such as copper and aluminum, have the advantages of high strength, good wear resistance, and easy processing, but metal materials have low thermal conductivity, poor flexibility, easy corrosion, and high thermal expansion coefficient. Compared with metal materials such as copper and aluminum, graphite materials have the characteristics of high temperature resistance, small thermal expansion coefficient, good thermal conductivity and electrical conductivity, good chemical stability, and high plasticity. In addition, graphite materials have good heat dissipation effect, which enables them to better conduct heat while preventing local overheating.

[0004] Artificial thermal conductive graphite film is a new type of graphite thermal conductive material. It is made of a polymer film with a special chemical structure that is carbonized and graphitized at high temperature. It has a similar atomic structure to graphite and has the characteristics of high thermal conductivity, light weight, soft and easy to cut, low thermal resistance and long-term stability. Among them, the artificial thermal conductive graphite film made from aromatic polyoxadiazole (POD) film by carbonization and graphitization has the advantages of low cost, higher thermal conductivity and small expansion coefficient. It has received more and more attention in recent years because the crystal arrangement of the graphite material prepared by it is more regular and orderly, and it is also called supercrystalline graphite.

[0005] The aromatic polyoxadiazole (POD) molecular chain contains oxadiazole rings and benzene ring structures, which make it have excellent heat resistance and a glass transition temperature higher than 400°C. In addition, the material has high strength, high modulus, excellent flame retardancy and resistance to acid and alkali chemicals. Its raw materials are simple and easy to obtain, and the price is low. Compared with other high-temperature resistant polymer materials, it also has obvious cost advantages. The thermal conductivity of supercrystalline graphite materials prepared from POD film can reach more than 1800W / (m·K), and its cost is only about 1 / 3 of the mainstream PI film material. However, due to the structure of the material itself, it is very easy for scaly fragments to fall off (commonly known as "powder loss") during the carbonization and graphitization process, which greatly affects the performance and subsequent application of the material itself. The defects in the crystal structure limit the performance of its high thermal conductivity and easily cause the risk of electronic component contamination. At the same time, it affects the operating environment and the health of operators, which restricts its large-scale promotion and application. In view of this, the problem of powder loss of POD film during carbonization and graphitization needs to be solved urgently.

[0006] CN110894291A discloses an aromatic polyoxadiazole film and a preparation method thereof. An aromatic dicarboxylic acid compound and a hydrazine salt are used as monomers, and a polycondensation reaction is carried out in fuming sulfuric acid to obtain an aromatic polyoxadiazole solution; the aromatic polyoxadiazole solution is extruded through a hanger-type casting die, and then transported to a dilute sulfuric acid coagulation bath for coagulation and molding to obtain a coagulated acid-containing wet primary casting film; the acid-containing wet primary casting film is washed to obtain a sulfuric acid-free primary casting film; the sulfuric acid-free primary casting film is tension-dried, heat-set at 200-350°C, and trimmed and wound to obtain the aromatic polyoxadiazole film. However, this patent cannot solve the problem of powder shedding during the carbonization and graphitization process of the POD film.

[0007] CN112979947A discloses an aromatic polyoxadiazole film and a method for preparing the film. The method uses terephthalic acid, phthalic acid derivatives and hydrazine salt as reaction raw materials, performs polycondensation reaction in fuming sulfuric acid to obtain an aromatic polyoxadiazole solution, extrude the aromatic polyoxadiazole solution through a hanger-type die, and then sequentially transport it to a first-stage coagulation bath, a second-stage coagulation bath and a third-stage coagulation bath for coagulation and forming to obtain a coagulated acid-containing wet primary cast film. After washing the acid-containing wet primary cast film, a sulfuric acid-free primary cast film is obtained; after biaxially stretching the sulfuric acid-free primary cast film, a heat setting treatment is performed at 300-450°C, and trimming and winding are performed to obtain the aromatic polyoxadiazole film. However, the patent adopts a three-stage step coagulation bath coagulation, the purpose of which is to increase the concentration difference between the polyoxadiazole solution and the sulfuric acid in the coagulation bath and increase the coagulation speed, so that a dense film cannot be obtained. This patent also cannot solve the problem of powder loss during the carbonization and graphitization process of the POD film.

[0008] No research reports on solving the problem of powder loss after carbonization and graphitization of aromatic polyoxadiazole (POD) films have been found in existing patents. Summary of the invention

[0009] The supercrystalline graphite thermal conductive film obtained by heat treatment of aromatic polyoxadiazole film has significant advantages such as higher thermal conductivity and lower cost compared with other thermal conductive materials. However, due to the structure of the material itself, it is very easy for scale-like fragments to fall off (commonly known as "powder loss") during the carbonization and graphitization of the film, which greatly affects the thermal conductivity of the material itself and brings a series of subsequent application problems. In view of the shortcomings of the prior art, the purpose of the present invention is to provide an aromatic polyoxadiazole film for preparing supercrystalline graphite that does not lose powder, and its preparation method and application, and creatively improve the synthesis, extrusion, solidification and stretching processes in its preparation process to obtain a POD film with high molecular weight, high cyclization rate, high orientation, high density and low porosity, and better comprehensive performance; after carbonization and graphitization, the film can effectively solve the "powder loss" problem, the crystal structure is more complete, the thermal conductivity is higher, and it has greater application potential.

[0010] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0011] In one aspect, the present invention provides a method for preparing an aromatic polyoxadiazole film, the method comprising the following steps:

[0012] S1: using fuming sulfuric acid as solvent and dehydrating agent, terephthalic acid and hydrazine sulfate as monomers, and benzoic acid as chain end-capping agent, a three-stage polycondensation reaction is carried out by step-wise addition to obtain an aromatic polyoxadiazole resin solution;

[0013] S2: The aromatic polyoxadiazole resin solution is pressure-oriented and transported to a molding die for extrusion to obtain an acid-containing primary cast film, which is then coagulated and formed in a single-stage coagulation bath to obtain a polyoxadiazole wet film;

[0014] S3: The polyoxadiazole wet film is washed to obtain an acid-free polyoxadiazole wet film; and then biaxially stretched, and then heat-set to obtain the aromatic polyoxadiazole film;

[0015] The three-stage polycondensation reaction in step S1 is as follows: the first stage has a reaction temperature of 80-90°C and a time of 1-2 hours; the second stage has a reaction temperature of 120-140°C and a time of 6-8 hours; the third stage has a reaction temperature of 180-200°C and a time of 1-2 hours;

[0016] The stepwise addition described in step S1 is that the amount of monomer added in the first stage of the three-stage polycondensation reaction is 50-80% of the total monomer amount, and the remaining 20-50% of the monomer is added in the second stage;

[0017] The pressurized orientation conveying in step S2 is first pressurized and extruded by a twin-screw extruder, and then pressurized and conveyed to a molding die by a gear pump.

[0018] The aromatic polyoxadiazole film prepared by the present invention does not produce the problem of "powder falling" after carbonization and graphitization. The obtained supercrystalline graphite film has a smooth and uniform appearance, a more complete crystal structure, and a higher thermal conductivity (>1900W / (m·K)). It does not pollute electronic components and does not affect the operating environment and the health of operators. It has better application prospects in the field of consumer electronics.

[0019] The principle of the present invention to solve the "powder falling" problem is as follows:

[0020] First, the prepared POD resin has a higher molecular weight and a higher cyclization rate. In the resin synthesis stage, the purpose of increasing the degree of polymerization and cyclization rate is achieved by controlling the reaction temperature, time and feeding method. Increasing the molecular weight can effectively reduce the generation of small molecule by-products; increasing the cyclization rate greatly reduces the number of straight-chain hydrazide groups in the molecular chain, increases the number of oxadiazole rings, and has a higher molecular chain bond energy. At low temperatures, the phenomenon of molecular chain breaking is less, thereby effectively reducing the probability of "powder loss" after heat treatment.

[0021] Second, the prepared POD membrane has high density, low film porosity and small pore size. The POD membrane is formed by a phase transition method and has a porous structure. A multi-stage coagulation bath with stepped concentration is used for conventional coagulation. The coagulation speed is accelerated by setting a concentration difference. However, multi-stage coagulation will increase the film porosity and enlarge the pore size due to excessive diffusion. Excessive porosity and excessive pore size will easily form defects during the carbonization and removal of non-carbon heteroatoms, leading to the "powder falling" phenomenon. In the coagulation and molding stage, the present invention adopts a high-concentration, low-temperature single-stage coagulation bath. The high-concentration coagulation bath can slow down the precipitation rate of sulfuric acid in the resin, making the film denser, with low film porosity and small pore size. At the same time, the lower coagulation bath temperature helps to absorb the heat generated during the film formation process, thereby inhibiting the degradation of the polymer.

[0022] Third, the prepared POD film has a higher degree of orientation and a more regular arrangement. This purpose is achieved through two steps. First, a twin-screw extruder is added in front of the gear pump at the feed end, which is conducive to the transportation of viscous materials and increases the pressure of the material during transportation. At the same time, the polymer molecular chains are oriented in an orderly manner under the action of the screw shear force, and the molecular chain orientation of the resin is preserved after extrusion and solidification; second, at the film-forming end, the washed POD wet film is biaxially stretched to further orient the molecular chains of the film. The obtained POD film has a higher degree of orientation and a regular arrangement. After high-temperature treatment, the atomic structure is highly ordered, which greatly suppresses the occurrence of the "powder falling" problem.

[0023] Through the above measures, a POD membrane with high molecular weight, high cyclization rate, high orientation degree, high density and low porosity was obtained. After carbonization and graphitization, the film can effectively solve the "powder falling" problem, has excellent comprehensive performance, and has broader application prospects.

[0024] In the present invention, the content of SO3 in the fuming sulfuric acid is 20-50 wt.% (e.g., 20 wt.%, 25 wt.%, 30 wt.%, 35 wt.%, 45 wt.%, 48 wt.% or 50 wt.%), and there is no black impurity, and the terephthalic acid and hydrazine sulfate need to be subjected to high-temperature drying and dehumidification treatment.

[0025] Preferably, the molar ratio of terephthalic acid to hydrazine sulfate is 1:(1-1.1), for example 1:1, 1:1.05, 1:1.08 or 1:1.1.

[0026] Preferably, the amount of benzoic acid used is 0.1-0.5% of the molar amount of terephthalic acid, for example 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%.

[0027] Preferably, the solid content of the polymerization reaction system is 10 to 20 wt.%, for example, 10 wt.%, 12 wt.%, 15 wt.%, 18 wt.% or 20 wt.%.

[0028] In the present invention, the three-stage polycondensation reaction in step S1 is a first stage, wherein the reaction temperature is 80-90°C (e.g., 80°C, 83°C, 85°C, 88°C or 90°C) and the time is 1-2h (e.g., 1h, 1.3h, 1.5h, 1.8h or 2h); a second stage, wherein the reaction temperature is 120-140°C (e.g., 120°C, 125°C, 128°C, 130°C, 135°C or 140°C) and the time is 6-8h (e.g., 6h, 7h or 8h); and a third stage, wherein the reaction temperature is 180°C-200°C (e.g., 180°C, 185°C, 190°C, 195°C or 200°C) and the time is 1-2h (e.g., 1h, 1.3h, 1.5h, 1.8h or 2h).

[0029] In the present invention, the stepwise addition described in step S1 is that the amount of monomer added in the first stage of the three-stage polycondensation reaction is 50-80% (for example, 50%, 55%, 58%, 60%, 65%, 70%, 75% or 80%) of the total monomer amount, and the remaining 20-50% (for example, 20%, 25%, 30%, 35%, 40%, 45% or 50%) of the monomer is added in the second stage.

[0030] Preferably, the aromatic polyoxadiazole resin solution obtained in step S1 has an intrinsic viscosity of not less than 2.4 g / dL, for example, 2.4 g / dL, 2.8 g / dL, 3 g / dL, 3.5 g / dL, 4 g / dL, 4.5 g / dL, 5 g / dL, 8 g / dL, etc.

[0031] Preferably, the cyclization rate of the aromatic polyoxadiazole resin obtained in step S1 is not less than 80%, for example, 80%, 85%, 88%, 90%, 95%, 98%, etc.

[0032] Preferably, in step S2, the aromatic polyoxadiazole resin solution is vacuum degassed and filtered before the pressurized orientation transport.

[0033] Preferably, the pressurized oriented conveying in step S2 is first extruded through a twin-screw extruder and then pressurized conveyed through a gear pump, the outlet pressure of the twin-screw extruder is 2~10MPa, for example, 2MPa, 3 MPa, 4 MPa, 5MPa, 6MPa, 7MPa, 8MPa, 9MPa or 10MPa, and the outlet pressure of the gear pump is 1~8MPa, for example, 1MPa, 2MPa, 3 MPa, 4 MPa, 5MPa, 6MPa, 7MPa or 8MPa.

[0034] Preferably, the single-stage coagulation bath in step S2 is a low-temperature, high-concentration sulfuric acid solution with a concentration of 45-60wt.%, for example, 45 wt.%, 48 wt.%, 50 wt.%, 55 wt.% or 60 wt.%, preferably 48-55wt.%; the temperature is 10-30°C, for example, 10°C, 13°C, 15°C, 18°C, 20°C, 25°C, 28°C or 30°C, preferably 10-20°C.

[0035] Preferably, the thickness of the polyoxadiazole wet film obtained in step S2 is 300-2000 μm, for example, 300 μm, 500 μm, 800 μm, 1000 μm, 1200 μm, 1500 μm, 1800 μm or 2000 μm.

[0036] Preferably, the washing in step S3 is performed using pure water.

[0037] Preferably, the longitudinal stretching ratio of the biaxial stretching in step S3 is 10% to 30%, for example, 10%, 15%, 18%, 20%, 23%, 25%, 28% or 30%, and the transverse stretching ratio is 10% to 30%, for example, 10%, 13%, 15%, 18%, 20%, 23%, 25%, 28% or 30%.

[0038] Preferably, the heat setting treatment in step S3 is first drying at 100-120°C (for example, 100°C, 105°C, 110°C, 115°C or 120°C), and then heat setting treatment at 200-250°C (for example, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C).

[0039] Preferably, the thickness of the aromatic polyoxadiazole film of the present invention is 40-300 μm, for example, 40 μm, 60 μm, 80 μm, 100 μm, 150 μm, 180 μm, 200 μm, 220 μm, 250 μm, 280 μm or 300 μm.

[0040] The preparation method of the present invention simplifies the process, is simple to operate, and saves costs. It can prepare aromatic polyoxadiazole films with high molecular weight, high cyclization rate, high orientation degree, high density, and low porosity. The films have excellent comprehensive properties such as physical mechanics and electrical insulation. Compared with other high-temperature resistant film materials such as PI (polyimide), they have greater cost advantages and are expected to be applied on a large scale in new fields such as electrical insulation and power batteries.

[0041] In another aspect, the present invention provides an aromatic polyoxadiazole film prepared by the preparation method described above.

[0042] On the other hand, the present invention provides a graphite film, which is obtained by carbonizing and graphitizing the aromatic polyoxadiazole film as described above.

[0043] Preferably, the graphite film has a thickness of 15 to 100 μm, for example, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] The aromatic polyoxadiazole film prepared by the present invention does not produce the problem of "powder falling" after carbonization and graphitization. The prepared supercrystalline graphite film has a smooth and uniform appearance, a more complete crystal structure, and a higher thermal conductivity (>1900W / (m·K)). It does not pollute electronic components, and does not affect the operating environment and the health of operators. It has better application prospects in the field of consumer electronics. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is a SEM image of the POD film prepared in Example 1 of the present invention;

[0047] Figure 2 This is a SEM image of the POD film prepared in Example 2 of the present invention;

[0048] Figure 3This is a SEM image of the POD film prepared in Example 3 of the present invention;

[0049] Figure 4 This is a SEM image of the POD film prepared in Comparative Example 1 of the present invention;

[0050] Figure 5 This is a SEM image of the POD film prepared in Comparative Example 2 of the present invention;

[0051] Figure 6 This is a SEM image of the POD film prepared in Comparative Example 3 of the present invention;

[0052] Figure 7 This is a SEM image of the POD film prepared in Comparative Example 4 of the present invention;

[0053] Figure 8 This is the SEM image of a commercially available POD film sample;

[0054] Fig. 9 This is an optical microscope photograph of a supercrystalline graphite film prepared by a POD film corresponding to Example 1 of the present invention, magnified 10 times;

[0055] Fig.10 This is an optical microscope photograph of a supercrystalline graphite film prepared from a POD film corresponding to Example 2 of the present invention, magnified 10 times.

[0056] Fig.11 This is an optical microscope photograph of a supercrystalline graphite film prepared by a POD film corresponding to Example 3 of the present invention, magnified 10 times;

[0057] Fig.12 This is an optical microscope photograph of a supercrystalline graphite film prepared by a POD film corresponding to Comparative Example 1 of the present invention, magnified 10 times;

[0058] Fig.13 This is an optical microscope photograph of a supercrystalline graphite film prepared by a POD film corresponding to Comparative Example 2 of the present invention, magnified 10 times;

[0059] Fig.14 This is an optical microscope photograph of a supercrystalline graphite film prepared by a POD film corresponding to Comparative Example 3 of the present invention, magnified 10 times;

[0060] Fig.15 This is an optical microscope photograph of a supercrystalline graphite film prepared by a POD film corresponding to Comparative Example 4 of the present invention, magnified 10 times;

[0061] Fig.16 This is an optical microscope photograph of a supercrystalline graphite film prepared from a commercially available POD film sample, magnified 10 times. DETAILED DESCRIPTION

[0062] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0063] Example 1

[0064] An aromatic polyoxadiazole film for preparing non-powdering supercrystalline graphite, the preparation method thereof is as follows:

[0065] S1: Terephthalic acid and hydrazine sulfate were mixed evenly at a molar ratio of 1:1.05, and polycondensed in 20% fuming sulfuric acid, and benzoic acid was used as a chain end capping agent (added at the end of the second stage) to synthesize a polyoxadiazole polymer solution, and the solid content of the reaction system was 15wt.%; the polycondensation reaction was divided into three stages: the first stage, the reaction temperature was 80°C, the time was 2h; the second stage, the reaction temperature was 120°C, the time was 8h; the third stage, the reaction temperature was 180°C, the time was 2h. 50% of the total monomers were added in the first stage, and the remaining 50% of the monomers were added at the beginning of the second stage.

[0066] S2: After vacuum degassing and filtration, the synthesized polyoxadiazole solution is first extruded through a twin-screw extruder and then pressurized and conveyed to a molding die through a gear pump. The outlet pressure of the twin-screw extruder is 6MPa, and the outlet pressure of the gear pump is 4MPa. The resin is extruded through the die onto a coagulation roller to obtain a primary cast film of the acid-containing polymer, which is then coagulated and formed in a low-temperature, high-concentration single-stage coagulation bath, wherein the low-temperature, high-concentration single-stage coagulation bath is a sulfuric acid solution with a concentration of 50wt.% and a temperature of 15°C, to obtain a coagulated polyoxadiazole wet film with a wet film thickness of 800μm.

[0067] S3: The polyoxadiazole wet film is fully washed to obtain an acid-free polyoxadiazole wet film; the acid-free polyoxadiazole wet film is biaxially stretched, first by 20% longitudinally and then by 20% transversely; and then heat-set, first by drying at 110°C and then by heat-setting at 200°C, to obtain the aromatic polyoxadiazole film having a film thickness of 120 μm.

[0068] The thickness of the supercrystalline graphite film obtained after carbonization and graphitization is 40μm.

[0069] Example 2

[0070] An aromatic polyoxadiazole film for preparing non-powdering supercrystalline graphite, the preparation method thereof is as follows:

[0071] S1: Terephthalic acid and hydrazine sulfate were mixed evenly at a molar ratio of 1:1.05, and polycondensed in 50% fuming sulfuric acid, and benzoic acid was used as a chain end capping agent (added at the end of the second stage) to synthesize a polyoxadiazole polymer solution, and the solid content of the reaction system was 20wt.%; the polycondensation reaction was divided into three stages: the first stage, the reaction temperature was 90°C, the time was 1.5h; the second stage, the reaction temperature was 130°C, the time was 7h; the third stage, the reaction temperature was 200°C, the time was 1h. 80% of the total monomers were added in the first stage, and the remaining 20% ​​of the monomers were added at the beginning of the second stage.

[0072] S2: The synthesized polyoxadiazole solution is subjected to vacuum degassing and filtration, and then extruded through a twin-screw extruder and then pressurized and conveyed to a molding die through a gear pump. The outlet pressure of the twin-screw extruder is 10MPa, and the outlet pressure of the gear pump is 7MPa. The resin is extruded through the die onto a coagulation roller to obtain a primary cast film of the acid-containing polymer, which is then coagulated and formed in a low-temperature, high-concentration single-stage coagulation bath, wherein the coagulation bath is a sulfuric acid solution with a concentration of 48wt.% and a temperature of 20°C, to obtain a coagulated polyoxadiazole wet film with a thickness of 2mm.

[0073] S3: The polyoxadiazole wet film is fully washed to obtain an acid-free polyoxadiazole wet film; the acid-free polyoxadiazole wet film is biaxially stretched, first by 15% longitudinally and then by 15% transversely; and then heat-set at 120°C for drying and then by 250°C for heat setting to obtain the aromatic polyoxadiazole film with a film thickness of 300 μm.

[0074] The thickness of the supercrystalline graphite film obtained after carbonization and graphitization is 100 μm.

[0075] Example 3

[0076] An aromatic polyoxadiazole film for preparing non-powdering supercrystalline graphite, the preparation method thereof is as follows:

[0077] S1: Terephthalic acid and hydrazine sulfate were mixed evenly at a molar ratio of 1:1.05, and polycondensed in 20% fuming sulfuric acid, and benzoic acid was used as a chain end capping agent (added at the end of the second stage) to synthesize a polyoxadiazole polymer solution, and the solid content of the reaction system was 10wt.%; the polycondensation reaction was divided into three stages: the first stage, the reaction temperature was 80°C, the time was 2h; the second stage, the reaction temperature was 140°C, the time was 6h; the third stage, the reaction temperature was 200°C, the time was 1h. 60% of the total monomers were added in the first stage, and the remaining 40% of the monomers were added at the beginning of the second stage.

[0078] S2: The synthesized polyoxadiazole solution is subjected to vacuum degassing and filtration, and then extruded through a twin-screw extruder and then pressurized and conveyed to a molding die through a gear pump. The outlet pressure of the twin-screw extruder is 2 MPa, and the outlet pressure of the gear pump is 2 MPa. The resin is extruded through the die onto a coagulation roller to obtain a primary cast film of the acid-containing polymer, which is then coagulated and formed in a low-temperature, high-concentration single-stage coagulation bath, wherein the coagulation bath is a sulfuric acid solution with a concentration of 55wt.% and a temperature of 10°C, to obtain a coagulated polyoxadiazole wet film with a wet film thickness of 300μm.

[0079] S3: The polyoxadiazole wet film is fully washed to obtain an acid-free polyoxadiazole wet film; the acid-free polyoxadiazole wet film is biaxially stretched, first by 30% longitudinally and then by 30% transversely; and then heat-set, first by drying at 100°C and then by heat-setting at 200°C, to obtain the aromatic polyoxadiazole film having a film thickness of 40 μm.

[0080] The thickness of the supercrystalline graphite film obtained after carbonization and graphitization is 15 μm.

[0081] Comparative Example 1

[0082] An aromatic polyoxadiazole film, the preparation method is as follows:

[0083] S1: Terephthalic acid and hydrazine sulfate were mixed evenly at a molar ratio of 1:1.05, and polycondensed in 20% fuming sulfuric acid, and benzoic acid was used as a chain end capping agent (added at the end of the second stage) to synthesize a polyoxadiazole polymer solution, and the solid content of the reaction system was 15wt.%; the polycondensation reaction was divided into three stages: the first stage, the reaction temperature was 80°C, the time was 2h; the second stage, the reaction temperature was 120°C, the time was 8h; the third stage, the reaction temperature was 180°C, the time was 2h. 50% of the total monomers were added in the first stage, and the remaining 50% of the monomers were added at the beginning of the second stage.

[0084] S2: After vacuum degassing and filtration, the synthesized polyoxadiazole solution is first extruded through a twin-screw extruder and then pressurized and conveyed to the molding die head through a gear pump. The outlet pressure of the twin-screw extruder is 6MPa, and the outlet pressure of the gear pump is 4MPa; the polymer acid-containing primary cast film is obtained, and then it is sequentially passed through the first coagulation bath, the second coagulation bath and the third coagulation bath for coagulation molding. Among them, the first coagulation bath is a 40wt.% dilute sulfuric acid solution at a temperature of 40°C, the second coagulation bath is a 25wt.% dilute sulfuric acid solution at a temperature of 50°C, and the third coagulation bath is a 10wt.% dilute sulfuric acid solution at a temperature of 20°C, to obtain a polyoxadiazole wet film with a wet film thickness of 800μm.

[0085] S3: The polyoxadiazole wet film is fully washed to obtain an acid-free polyoxadiazole wet film; the acid-free polyoxadiazole wet film is biaxially stretched, first by 20% longitudinally and then by 20% transversely; and then heat-set, first by drying at 110°C and then by heat-setting at 200°C, to obtain the aromatic polyoxadiazole film having a film thickness of 120 μm.

[0086] The thickness of the supercrystalline graphite film obtained after carbonization and graphitization is 40μm.

[0087] The difference between Comparative Example 1 and Example 1 is that the coagulation process of Comparative Example 1 adopts three-stage step coagulation bath coagulation.

[0088] Comparative Example 2

[0089] An aromatic polyoxadiazole film, the preparation method is as follows:

[0090] S1: Terephthalic acid and hydrazine sulfate are mixed evenly at a molar ratio of 1:1.05, and polycondensed in 20% fuming sulfuric acid, and benzoic acid is used as a chain end-capping agent (added at the end of the second stage) to synthesize a polyoxadiazole polymer solution, and the solid content of the reaction system is 15wt.%; the polycondensation reaction is divided into three stages: the first stage, the reaction temperature is 100°C, the time is 4h; the second stage, the reaction temperature is 140°C, the time is 4h; the third stage, the reaction temperature is 150°C, the time is 2h. In the polycondensation reaction, all materials are added to the device, and then the temperature is adjusted separately to carry out the three-stage reaction (that is, no step-by-step feeding).

[0091] S2: The synthesized polyoxadiazole solution is vacuum degassed and filtered, and then extruded through a twin-screw extruder and then pressurized and conveyed to a molding die through a gear pump. The outlet pressure of the twin-screw extruder is 6 MPa, and the outlet pressure of the gear pump is 4 MPa. The resin is extruded through the die onto a coagulation roller to obtain a primary cast film of the acid-containing polymer, which is then coagulated and formed in a low-temperature, high-concentration single-stage coagulation bath, wherein the coagulation bath is a sulfuric acid solution with a concentration of 50wt.% and a temperature of 15°C, to obtain a coagulated polyoxadiazole wet film with a wet film thickness of 800μm.

[0092] S3: The polyoxadiazole wet film is fully washed to obtain an acid-free polyoxadiazole wet film; the acid-free polyoxadiazole wet film is biaxially stretched, first longitudinally stretched by 20%, then transversely stretched by 20%; then heat-set, first dried at 110°C, then heat-set at 200°C, to obtain the aromatic polyoxadiazole film, the film thickness is 120μm. The supercrystalline graphite film obtained after carbonization and graphitization has a thickness of 40μm.

[0093] The difference between Comparative Example 2 and Example 1 is that the polymerization process of Comparative Example 2 adopts a conventional three-stage synthesis method.

[0094] Comparative Example 3

[0095] An aromatic polyoxadiazole film, the preparation method is as follows:

[0096] S1: Terephthalic acid and hydrazine sulfate were mixed evenly at a molar ratio of 1:1.05, and polycondensed in 20% fuming sulfuric acid, and benzoic acid was used as a chain end capping agent (added at the end of the second stage) to synthesize a polyoxadiazole polymer solution, and the solid content of the reaction system was 15wt.%; the polycondensation reaction was divided into three stages: the first stage, the reaction temperature was 80°C, the time was 2h; the second stage, the reaction temperature was 120°C, the time was 8h; the third stage, the reaction temperature was 180°C, the time was 2h. 50% of the total monomers were added in the first stage, and the remaining 50% of the monomers were added at the beginning of the second stage.

[0097] S2: The synthesized polyoxadiazole solution is vacuum degassed and filtered, then transported to the die after being metered by a gear pump, extruded onto a coagulation roller through the die to obtain a primary cast film of the acid-containing polymer, and then coagulated and formed in a low-temperature, high-concentration single-stage coagulation bath, wherein the coagulation bath is a sulfuric acid solution with a concentration of 50wt.% and a temperature of 15°C, to obtain a coagulated polyoxadiazole wet film with a wet film thickness of 700μm.

[0098] S3: The polyoxadiazole wet film is fully washed to obtain an acid-free polyoxadiazole wet film; the acid-free polyoxadiazole wet film is directly subjected to heat setting treatment, first dried at 110°C, and then subjected to heat setting treatment at 200°C to obtain the aromatic polyoxadiazole film, the film thickness of which is 120 μm. The supercrystalline graphite film obtained after carbonization and graphitization of the film has a thickness of 40 μm.

[0099] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 adopts conventional material transportation and does not perform biaxial stretching on the wet film.

[0100] Comparative Example 4

[0101] An aromatic polyoxadiazole film, the preparation method is as follows:

[0102] S1: Terephthalic acid and hydrazine sulfate are mixed evenly at a molar ratio of 1:1.05, and a polycondensation reaction is carried out in 20% fuming sulfuric acid. Benzoic acid is used as a chain end-capping agent (added at the end of the second stage) to synthesize a polyoxadiazole polymer solution, and the solid content of the reaction system is 8wt.%; the polycondensation reaction is divided into three stages: the first stage, the reaction temperature is 100°C, the time is 4h; the second stage, the reaction temperature is 140°C, the time is 4h; the third stage, the reaction temperature is 150°C, the time is 2h, in the polycondensation reaction, all materials are added to the device, and then the temperature is adjusted separately to carry out the three-stage reaction (i.e., no step-by-step feeding is carried out).

[0103] S2: The synthesized polyoxadiazole solution is vacuum degassed and filtered, then metered by a gear pump and transported to the die head, extruded through the die head onto a coagulation roller, to obtain a primary cast film of the acid-containing polymer, and then sequentially passed through a first coagulation bath, a second coagulation bath, and a third coagulation bath for coagulation molding. The first coagulation bath is a 40wt.% dilute sulfuric acid solution at a temperature of 40°C, the second coagulation bath is a 25wt.% dilute sulfuric acid solution at a temperature of 50°C, and the third coagulation bath is a 10wt.% dilute sulfuric acid solution at a temperature of 20°C, to obtain a polyoxadiazole wet film with a wet film thickness of 700μm.

[0104] S3: The polyoxadiazole wet film is fully washed to obtain an acid-free polyoxadiazole wet film; the acid-free polyoxadiazole wet film is directly subjected to heat setting treatment, first dried at 110°C, and then subjected to heat setting treatment at 200°C to obtain the aromatic polyoxadiazole film, the film thickness of which is 120 μm. The supercrystalline graphite film obtained after carbonization and graphitization of the film has a thickness of 40 μm.

[0105] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 adopts a conventional film-making route, that is, a conventional synthesis method, three-stage coagulation, conventional material transportation, and no biaxial stretching of the wet film is performed.

[0106] The carbonization and graphitization process is as follows: the POD film and carbon paper are stacked layer by layer, placed in a high-temperature carbonization furnace, and under vacuum conditions, the heating rate is controlled to be 2℃ / min and the temperature is raised to 1400℃, and the temperature is kept for 3 hours for high-temperature carbonization; after the carbonization cooling is completed, the film is taken out and placed in a high-temperature graphitization furnace, and under inert gas conditions, the heating rate is controlled to be 3℃ / min and the temperature is raised to 3000℃, and the temperature is kept for 4 hours for high-temperature graphitization; after the graphitization is completed, the film is taken out and calendered to obtain a supercrystalline graphite film.

[0107] The physical properties and carbonization and graphitization results of the POD films corresponding to Examples 1 to 3, Comparative Examples 1 to 4 and commercially available samples are shown in Table 1 below.

[0108] Table 1

[0109]

[0110] The test method is as follows:

[0111] (1) Intrinsic viscosity: Prepare a POD solution with a concentration of 0.3 g / 100 mL using concentrated sulfuric acid (95%-98%) as solvent. Measure the effluent time of the sample solution at (30±0.1)°C using an Ubbelohde viscometer (capillary diameter 0.9-1.0 mm). Compare the effluent time with that of the concentrated sulfuric acid solvent to calculate the relative viscosity and specific viscosity. Use the extrapolation method to derive the intrinsic viscosity of the sample.

[0112] (2) Cyclization rate: After washing and drying, the POD resin is tested for C, H, and N contents by an element analyzer, and the O content is calculated. The cyclization rate is calculated according to the following formula: Cyclization rate (CD) = (19.75-O POD ) / (19.75-11.11)×100%, where 19.75 and 11.11 are the O contents of pure p-phenylene hydrazide and pure poly(p-phenylene-1,3,4-oxadiazole) respectively; O POD is the actual O content of the POD sample to be tested.

[0113] (3) Birefringence (characterization of in-plane orientation): Birefringence was tested using a 2010M prism coupler from Metricon, USA, and the refractive index of the film formed on a 7.62 cm silicon wafer was measured at room temperature at a wavelength of 633 nm. The in-plane (n TE ) and out-of-plane (n TM ) refractive index. TE measurement of the electric field in the film plane provides the in-plane refractive index (n TE ⫽nx,y), while the TM measurement with the electric field out of plane provides the in-plane refractive index (n TM ⫽nz). The in-plane orientation of the film is represented by the birefringence value (Δn) of the film, which satisfies the following equation:

[0114] Δn = n TE -n TM .

[0115] (4) Porosity: Tested in accordance with GB / T 33052-2016 “Determination of porosity of microporous functional films - Hexadecane absorption method”.

[0116] (5) Thickness, density, tensile strength, elongation at break, electrical strength: tested in accordance with GB / T 13542.2-2021 "Films for electrical insulation - Part 2: Test methods".

[0117] (6) Thermal conductivity: Refer to ASTM-E1461 "Standard test method for determination of fixed thermal conductivity by flash method" and use LFA467 laser thermal conductivity meter (NETZSCH, Germany) to test at 25°C.

[0118] (7) Powder loss test method: Gently rub the surface of the graphite film with white paper and visually observe whether there are scaly debris or powdery solids.

[0119] It can be seen from the data in the above table that the aromatic polyoxadiazole film prepared by the method of the present invention in Examples 1 to 3 has a high molecular weight, high cyclization rate, high orientation degree, high density, low porosity, and better comprehensive properties such as mechanical strength and electrical insulation. After carbonization and graphitization, the film can effectively solve the "powder loss" problem, the crystal structure is more complete, and the thermal conductivity is higher (>1900W / (m·K)). Comparative Example 1 uses a three-stage step coagulation bath. The higher the coagulation bath temperature, the more serious the porosity and degradation of the film, so the "powder loss" situation is also relatively serious. In Comparative Example 2, the traditional three-stage polymerization method is used. In comparison, the degree of polymerization and cyclization rate are not high, and there are more small molecular by-products in the polymer, so there are more powder loss. In Comparative Example 3, there is a lack of pressure orientation and biaxial stretching process of wet film, the molecular orientation of the polymer is reduced, the overall performance is also reduced, and there is a little powder loss. In Comparative Example 4, the conventional film-making route was adopted, i.e., conventional synthesis, three-stage coagulation, conventional material transportation, and no biaxial stretching of the wet film. The POD film obtained had low molecular weight, low cyclization rate, low density, low orientation degree, and large porosity, and thus the powder loss was the most serious. The performance of the commercially available POD film sample was similar to that of Comparative Example 4, and it is speculated that the process of the two should be basically the same.

[0120] The aromatic polyoxadiazole films prepared in Examples 1 to 3 and Comparative Examples 1 to 4 and commercially available POD film samples were characterized using a scanning electron microscope (SEM, model: V018, ZEISS, Germany). Figure 1 to Figure 8 As shown, it can be seen that the POD membranes prepared in Examples 1 to 3 have a smoother and more uniform appearance, a higher density, and no obvious defects such as bubbles, pinholes, and pores; the POD membrane prepared in Comparative Example 1 has obvious bubbles; the POD membrane prepared in Comparative Example 2 has only a few bubbles; the POD membrane prepared in Comparative Example 3 has a small amount of bubbles; the POD membrane prepared in Comparative Example 4 has obvious defects such as pinholes; the commercially available POD membrane is not flat enough, and also has defects such as bubbles and pinholes.

[0121] The supercrystalline graphite films prepared in Examples 1 to 3, Comparative Examples 1 to 4 and commercially available POD film samples were characterized using an optical microscope (model: Axiolab 5, ZEISS, Germany). The results are as follows: Figures 9 to 16As shown, it can be seen that the supercrystalline graphite films prepared in Examples 1 to 3 are flat and uniform, orderly oriented, and have no protruding flaky objects; the supercrystalline graphite films prepared in Comparative Examples 1 to 4 and commercially available POD film samples all have flaky protrusions to varying degrees, and their appearance is consistent with the scaly fragments observed by visual inspection, that is, they all have powder loss to varying degrees, and the size is basically consistent with the visual inspection.

[0122] The method for preparing an aromatic polyoxadiazole film provided by the present invention obtains a film with high molecular weight, high cyclization rate, high orientation degree, high density and low porosity by creatively improving the synthesis, extrusion, solidification and stretching processes in the preparation process, and has better comprehensive performance; after carbonization and graphitization, the film can effectively solve the "powder falling" problem, has a more complete crystal structure, and has a higher thermal conductivity, and has greater application potential.

[0123] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing an aromatic polyoxadiazole film, characterized in that: The preparation method comprises the following steps: S1: using fuming sulfuric acid as solvent and dehydrating agent, terephthalic acid and hydrazine sulfate as monomers, and benzoic acid as chain end-capping agent, a three-stage polycondensation reaction is carried out by step-wise addition to obtain an aromatic polyoxadiazole resin solution; S2: The aromatic polyoxadiazole resin solution is pressure-oriented and transported to a molding die for extrusion to obtain an acid-containing primary cast film, which is then coagulated and formed in a single-stage coagulation bath to obtain a polyoxadiazole wet film; S3: washing the polyoxadiazole wet film to obtain an acid-free polyoxadiazole wet film; then biaxially stretching the film, and then performing heat setting treatment to obtain the aromatic polyoxadiazole film; The three-stage polycondensation reaction in step S1 is as follows: the first stage has a reaction temperature of 80-90°C and a time of 1-2 hours; the second stage has a reaction temperature of 120-140°C and a time of 6-8 hours; the third stage has a reaction temperature of 180-200°C and a time of 1-2 hours; The stepwise addition described in step S1 is that the amount of monomer added in the first stage of the three-stage polycondensation reaction is 50-80% of the total monomer amount, and the remaining 20-50% of the monomer is added in the second stage; The pressurized orientation conveying in step S2 is firstly pressurized and extruded by a twin-screw extruder, and then pressurized and conveyed to a molding die by a gear pump; The single-stage coagulation bath in step S2 is a sulfuric acid solution with a concentration of 45-60wt.% and a temperature of 10-30°C.

2. The preparation method according to claim 1, characterized in that: The molar ratio of terephthalic acid to hydrazine sulfate is 1:(1~1.1); The molar ratio of benzoic acid to terephthalic acid is (0.1-0.5%):1; The intrinsic viscosity of the aromatic polyoxadiazole resin solution obtained in step S1 is not less than 2.4 g / dL, and the cyclization rate of the aromatic polyoxadiazole resin obtained in step S1 is not less than 80%.

3. The preparation method according to claim 1, characterized in that: Step S2: Before the pressure-oriented transport, the aromatic polyoxadiazole resin solution is vacuum degassed and filtered.

4. The preparation method according to claim 1, characterized in that: The outlet pressure of the twin-screw extruder is 2-10 MPa, and the outlet pressure of the gear pump is 1-8 MPa.

5. The preparation method according to claim 1, characterized in that: The thickness of the polyoxadiazole wet film obtained in step S2 is 300-2000 μm.

6. The preparation method according to claim 1, characterized in that: The washing in step S3 is washing with pure water; The longitudinal stretching ratio of the biaxial stretching in step S3 is 10% to 30%, and the transverse stretching ratio is 10% to 30%; The heat setting treatment in step S3 is first drying at 100-120°C and then heat setting treatment at 200-250°C.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The thickness of the aromatic polyoxadiazole film is 40-300 μm.

8. An aromatic polyoxadiazole film prepared by the preparation method according to any one of claims 1 to 6.

9. A graphite film, characterized in that: The graphite film is obtained by carbonizing and graphitizing the aromatic polyoxadiazole film as claimed in claim 8.

Citation Information

Patent Citations

  • Aromatic polyoxadiazole film and preparation method thereof

    CN110894291A

  • Aromatic polyoxadiazole, aromatic polyoxadiazole film and preparation method of aromatic polyoxadiazole film

    CN112979947A

Cited By

  • High-thermal-conductivity graphite film, preparation method and heat dissipation assembly

    CN122212119A